Dosimetric Properties of Dy-doped Li2O-B2O3 Glasses - Kato, Takumi; Nishikawa, Akihiro; Nakauchi, Daisuke; Kawaguchi, Noriaki; Yanagida, Takayuki (Sensors and Materials, 2025)
As dosimetric materials, undoped and Dy-doped 33.3LiO–66.7B2O3 glasses were synthesized by the melt-quenching method. Their photoluminescence and thermally stimulated luminescence spectra showed several emission lines. A broad glow peak was observed at ~75 ℃ in the Dydoped samples, while the undoped sample showed no glow peaks. A linear relationship between irradiation dose and thermally stimulated luminescence intensity was confirmed from 1 to 1000 mGy when the 0.5% Dy-doped glass was exposed to different doses of X-ray radiation.